Approaching a revolution in hemiparasitic plant biology? A commentary on 'Distinguishing carbon gains from photosynthesis and heterotrophy in C3-hemiparasite-C3-host-pairs' - Těšitel, Jakub; Těšitelová, Tamara (Annals of botany, 2022)
This article comments on: Philipp Giesemann and Gerhard Gebauer, Distinguishing carbon gains from photosynthesis and heterotrophy in C3-hemiparasite–C3-host pairs, Annals of Botany, Volume 129, Issue 6, 12 May 2022, Pages 647–656 https://doi.org/10.1093/aob/mcab153
Keywords: Carbon; mixotrophy; Orobanchaceae; stable isotope; biologie; Heterotrophic Processes; heterotrophy; Biology; Photosynthesis; Santalales; parasitic plant; uhlík; heterotrofní procesy; Hemiparasitism; fotosyntéza